Analisis Peran Media Sosial sebagai Sarana Literasi Kesehatan Mental bagi Generasi Z dalam Menghadapi Tekanan Psikososial Pascapandemi - Sandy Amalia; Fatiha Munawaroh; Arina Syafrie Malun (Gema Cendekia Institute, 2025)
Post-COVID-19 pandemic, Generation Z faces increased psychosocial distress characterized by anxiety, stress, and difficulties in social adaptation. At the same time, social media has become an integral part of this generation's lives and has the potential to act as a means of mental health literacy. This study aims to analyze the role of social media as a medium for mental health literacy for Generation Z in coping with post-pandemic psychosocial distress. The study used a quantitative approach with a survey design, involving Generation Z respondents who actively use social media. Data were collected through a structured questionnaire that measured social media usage patterns, mental health literacy levels, and psychosocial distress levels, then analyzed using descriptive and inferential statistical techniques. The results show that Generation Z has a high intensity of social media use and is actively exposed to mental health content. Respondents' mental health literacy levels are in the moderate category, with relatively good abilities in recognizing emotional problems, but still limited in in-depth understanding and application of appropriate coping strategies. Social media plays a role as a facilitator for increasing mental health literacy, especially through relevant and easily accessible psychoeducational content. Mental health literacy has been shown to contribute to reducing levels of psychosocial distress, thus acting as a protective factor for the psychological well-being of Generation Z. However, without adequate literacy, social media also has the potential to amplify psychosocial distress through exposure to negative content and misinformation. This study emphasizes the importance of strengthening social media-based mental health literacy as a promotive and preventive strategy for Generation Z.